Автономія: поняття, принципи, класифікація - Мяловицька, Н.А. (Альманах права, 2012)
В статті досліджується поняття автономії в конституційному праві, принципи їх утворення та критерії класифікації. В статье исследуется понятие автономии в конституционном праве, принципы их образования и критерии классификации. The article is dedicated to the understanding of autonomy concept in constitutional law. Author’s definition of autonomy as a form of state in which the state pays attention to national, historical, economic, geographical, religious and other characteristics of the population of selected areas giving them enhanced rights for local government and provides the political and cultural demands of different forms of these groups by their extraterritorial self. We consider a variety of forms of autonomy, principles of formation and classification criteria. Defined two main types of autonomy: territorial and extraterritorial (cultural). By indicating that autonomous movements it is possible to improve the state system, the implementation of state power decentralization, optimization of local management and local government, to protect cultural values of peoples living in this country.